IMPLEMENTASI PERATURAN MENTERI DESA, PEMBANGUNAN DAERAH TERTINGGAL, DAN TRANSMIGRASI NOMOR 2 TAHUN 2016 TENTANG INDEKS DESA MEMBANGUN (STUDI KASUS DESA GUNUNG SARI KAMPAR, RIAU) - Ashari, Ahmad Gozali Fathurrahman; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
An effort to support the disadvantaged village reduction program that entered the agenda of RPJMN 2015-2019 is to maximize the potential of the village owned. The central government makes the village index build (IDM) in the form of ministerial regulation of village, disadvantaged regional development and transmigration number 2 year 2016 which is used to measure the country's independence direction with three main indicators, namely social, economic, and environment. Gunung Sari Village Kampar District which is a self-contained village in Riau province. With the status of Independent village, Gunung Sari Village government and village community can not implement the IDM with maximum. The purpose of this research is to know how the IDM implementation in Gunung Sari Village Kampar District. The theory used is the Smith theory which is the implementation theory of the bottom up model with four indicators: idealized policy, Target GRUOP, implementing organization, and Enviromental factor as well as three indicators of IDM, Social Security Index, economic endurance index, and environmental resilience index. This method of study is to use a qualitative method with a case study approach. The results of this research show that: first, implentation regulation of the village minister about the village Building Index (IDM) in Gunung Sari village is still not optimal. Secondly, the factors that inhibit the implementation of ministerial regulation on Village Index Building (IDM) in Gunung Sari village, namely, incomplete education facility, lack of access to clean water and landfills, and absence of the country's flagship product as a source of income that can reach the economy of village community. The advice in this research should be that village governments can focus more on Community empowerment programs. Keywords: Village Development Index, Public Policy, Implementation